Determination of inorganic radio-iodides in compounds labelled with 131I by thin layer chromatography II - Bianco de Salas, Gladis N.; Pisarello de Troparevsky, M. L.; Mitta, Aldo Eduardo Antonio (Elsevier BV, 1967)
Fil: Bianco de Salas, Gladis N. Comisión Nacional de Energía Atómica; Argentina